Epigenetic regulation of memory: implications in human cognitive disorders - Kramer, Jamie M. (Biomolecular concepts, 2013)
Epigenetic modification of chromatin structure is an important mechanism in the regulation of gene expression. Recent studies have shown that dynamic regulation of chromatin structure occurs in response to neuronal stimulation associated with learning and memory. Learning-induced chromatin modifications include DNA methylation, histone acetylation, histone phosphorylation and histone methylation. Studies in animal models have used genetic and pharmacological methods to manipulate the epigenetic machinery in the brain during learning and memory formation. In general, these studies suggest that epigenetic regulation of chromatin structure is essential for long term memory (LTM) consolidation, which is known to require new gene transcription. Analysis of animal models has also implicated epigenetic mechanisms in impaired cognition associated with aging, neurodegenerative disease, and intellectual disability (ID). Recently, it has been shown that a subset of ID disorders and autism are caused by disruption of specific chromatin modification complexes that are involved in nuclear hormone receptor mediated transcriptional regulation. This review provides an overview of chromatin modifications that are implicated in learning and memory and discusses the role of chromatin modifying proteins in learning-induced transcriptional regulation and human cognitive disorders.